Jean-Marie Gleize, Emmanuel Hocquard, and the Challenge of Lyricism - Glenn W. Fetzer (Studies in 20th & 21st Century Literature, 2005)
Within the past decade, one of the most pressing questions of poetry in France has been the continuing viability of lyricism. Recent models of perceiving the nature of lyricism shift the focus from formal and thematic considerations to pragmatic ones. As Hocquard's Un test de solitude: sonnets (1998) and Gleize's Non (1999) illustrate, the challenge of the lyric today serves to sharpen the sense of alterity and gives evidence of lyricism's capacity for renewal. More specifically, in presenting a reading of sonnets from both writers, this paper shows that the debates on the nature and "recurrence" of lyricism foreground the relational mode, above all, and give witness to the capacity of the lyric to withstand, to test, and ultimately, to reinvent itself.
Keywords: poetry; lyricism; Hocquard; Un test de solitude: sonnets; Gleize; Non; sonnet; recurrence; recurrence of lyricism